Circus stories in basic vocabulary - Dolch, Edward William 1889-1961.; Dolch, Marguerite Pierce 1891-.; Wallace, Dee. (Champaign, Ill. Garrard Press, 1956)
Eighteen stories, based on true episodes, about the people and animals in a circus, such as the first woman trapeze artist to do the triple somersault, and the elephant who stole lemonade.
Keywords: Circus -- Juvenile fiction; Circus -- Fiction